Using language games to motivate the first year students in speaking classes at Thai Nguyen Medical College - Hoang, Thi Thu Hoai (University of Languages and International Studies, 2017)
This minor thesis was conducted with an attempt to investigate the effectiveness of language games in teaching speaking to the first year students non- English majors at Thai Nguyen Medical College.